Bad intent eaudiobook A maggie macgowen mystery. - Hornsby, Wendy (Mysterious Press-HighBridge Audio Classics., 2014)
When a shady politician frames three police officers by dredging up dirty allegations in order to gain the minority vote, investigative filmmaker Maggie MacGowen becomes determined to uncover the truth.